A mixed-integer programming model for the replacement strategy of an egg farm - Leow, S. K. (1987)
This paper presents a mixed-integer programming model for the replacement programme of an egg farm. The model incorporates force moulting as an integral part of the replacement programme. For maximum economic returns. it also takes into consideration the variability of egg prices throughout the year. The model was tested using data from the commercial Poultry Unit in Universiti Pertanian Malaysia. The resulting solutions are then presented and their implications discussed.